Kontribusi Nilai-nilai Keimanan dan Kemanusiaan Persaudaraan Cinta Tanah Air Indonesia - Mukhammad Abdullah (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2017)
The existence of the PCTA-I (Persaudaraan Cinta Tanah Air-Indonesia/Brotherhood for the Love of Indonesia Homeland) plays a pivotal role, especially for underprivileged people regardless of their religion and faith, tribe, and race. This organization has been, therefore, undeniably desirable to help the Indonesian society overcome its social problems. Focusing its discussion on the PCTA-I, this article seeks to answer such questions as to how this organization has been initiated, what it does to help overcome national problems, and the obstacles it faces in implementing the programs, and how it does it overcome such obstacles? A number of leaders and members of the PCTA-I Central Board have been interviewed. The murshid of the Tarekat Ṣiddīqīyah has been among the main informants of this study. Employing a qualitative approach by focusing on interviews, questionnaires, and documentation as the sources of data, the study indicates that the PCTA-I has efficiently implemented its programs due to solid participation and robust support of its voluntary community. Through its programs, the PCTA-I attempts to build what so-called “the soul of society” in order to achieve a civilized and enlightened future for Indonesia.